High Q femtoREGEN™ UC laser systems for industrial microprocessing applications - Matylitsky, V. V.; Kubis, Peter; Brabec, Christoph; Au, J. Aus Der (Frontiers in Ultrafast Optics: Biomedical, Scientific, and Industrial Applications XII, 2012)
High average power, high repetition rate femtosecond lasers with μJ pulse energies are increasingly used for bio-medical and material processing applications. With the introduction of femtosecond laser systems such as the High Q femtoREGEN™ UC platform, micro-processing of solid targets with femtosecond laser pulses have obtained new perspectives for industrial applications. The unique advantage of material processing with sub-picosecond lasers is efficient, fast and localized energy deposition, which leads to high ablation efficiency and accuracy in nearly all kinds of solid materials. In this paper, we will show aspects of the design and performance of the femtoREGEN™ UC industrial laser system and give an overview of actual applications. © 2012 SPI
Keywords: Ablation; Femtosecond laser pulse; Micro-processing; Ultrafast laser